Anti-Plasmodial Effects of June Plum Tree (Spondias dulcis) Bark Aqueous Extract on Albino Mice Infected with Plasmodium berghei - Elele, Kingsley; Ojuka, Kenneth Isoboye; Biibaloo, Legborsi Livinus (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Malaria, caused by Plasmodium parasites and transmitted by Anopheles mosquitoes, remains a major global health issue. Drug resistance to conventional antimalarial medications underscores the need for alternative treatments. June plum (Spondias dulcis), a tropical plant traditionally used for its medicinal properties, may offer a new avenue for antimalarial therapy. This study aims to evaluate the anti-plasmodial effects of the aqueous extract of Spondias dulcis bark on albino mice infected with Plasmodium berghei berghei and to assess its potential as a new treatment for malaria. The fresh bark of Spondias dulcis was extracted using distilled water. The aqueous extract was characterized for its phytochemical content and tested for antimalarial activity in albino mice infected with P. berghei berghei. Mice were divided into groups: control (no treatment), infected-untreated, infected-standard antimalarial drug-treated, and infected-extract-treated. Parasitemia levels, clinical symptoms, and body weight changes were monitored. Toxicity was assessed through post-mortem examination. The aqueous extract of Spondias dulcis bark yielded 8.5% extract with notable phytochemicals including flavonoids, tannins, and saponins. Mice treated with the extract showed a mean parasitemia reduction to 31.4% by day 14, which was significantly lower than the untreated group but less effective than standard antimalarial drugs (18.7% parasitemia). Clinical improvements and slight weight loss were observed, with no significant adverse effects noted in toxicity assessments. The aqueous extract of Spondias dulcis bark demonstrates moderate antimalarial activity in the rodent model and shows potential as a complementary treatment for malaria. While less effective than standard drugs, it provides a promising alternative that warrants further research to optimize its efficacy and explore its mechanisms of action.